2020
DOI: 10.1155/2020/9816204
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer and Colour Analysis during Vacuum Frying of Colombian Coastal Carimañola

Abstract: This study is aimed at analysing the effect of vacuum frying on the kinetic parameters of mass transfer, the CIE L∗a∗b∗ colour parameters of the Carimañola. For the kinetic analysis, the moisture and oil content were measured by means of an experimental design consisting of two factors: frying time with seven levels (60, 120, 180, 240, 300, 420, and 540 s) and frying temperature with three levels (120, 130, and 140°C). The diffusivity coefficient, the moisture transfer rate, and the oil adsorption rate, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Vacuum frying is a new food processing technology developed in the late 1960s and early 1970s that is carried out under pressures well below atmospheric levels. Compared with conventional frying, vacuum frying has several advantages: (1) the oil absorption rate is decreased [48];…”
Section: Vacuum Fryingmentioning
confidence: 99%
“…Vacuum frying is a new food processing technology developed in the late 1960s and early 1970s that is carried out under pressures well below atmospheric levels. Compared with conventional frying, vacuum frying has several advantages: (1) the oil absorption rate is decreased [48];…”
Section: Vacuum Fryingmentioning
confidence: 99%
“…The main ingredient in Carimañolas is cassava dough; it is often stuffed with meat or cheese and then subjected to frying treatments. This type of product, mostly handmade, represents a way of taking advantage and transforming cassava into by-products with greater added value, since they are more attractive to consumers due to the sensory properties conferred in the frying process [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In thermal treatments, these properties depend on the temperature applied and the chemical composition of the food matrix, in addition to allowing calculation of the amounts of heat and time required for processing each food [ 14 ]. Caro et al [ 5 ] demonstrated that the characteristics of the coastal Carimañola are influenced by processing conditions, temperature, and frying time.…”
Section: Introductionmentioning
confidence: 99%